SANTIAGO CAMPIÓN, R. y BERGMANN, J. (2018). Aprender al revés. Flipped learning 3.0 y metodologías activas en el aula. Barcelona: Paidós Educación, 240 páginas, ISBN 978-84-493-3486-3 - Esther García Zabaleta (Universidad de La Rioja, 2020)
SANTIAGO CAMPIÓN, R. y BERGMANN, J. (2018). Aprender al revés. Flipped learning 3.0 y metodologías activas en el aula. Barcelona: Paidós Educación, 240 páginas, ISBN 978-84-493-3486-3.